The Effects Of Transformational Leadership And Organizational Culture On Employee's Performance (Case Study at Nippon Paint Company Branch in Bengkulu City) - Mia Tri Agustina; Tito Irwanto; Eska Prima Monique D (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to determine the calculation and effect of leadership and organizational culture on employee’s performance at Nippon Paint company branch in Bengkulu City. The analytical method used in the research is the quantitative method. Based on research results, Transformational Leadership has a significant effect on Employee’s Performance because tcount (2.753) is greater than ttable (1.674) with a significant value of 0.008 < 0.05. This illustrates that the better the transformational leadership at Nippon Paint company branch in Bengkulu City, the more employee’s performance will increase. Organizational culture does not have a significant effect on employee’s performance because tcount (0.771) is smaller than ttable (1.674) with a significant value of 0.445 > 0.005. This illustrates that employees at Nippon Paint company branch in Bengkulu City. From the simultaneous test results we can see that there is a significant effect between transformational leadership and organizational culture on the employee’s performance at Nippon Paint company branch in Bengkulu City together because the value of Fcount > Ftable is 4.581 > 3.18 with a significance of 0.015 < 0, 05. From the results of the coefficient of determination test, the R square value is 0.155 or 15.5%. It can be concluded that there is a variable effect on employee’s performance of 15.5%. The remaining 84.5% is effected by variables outside this research.